Guardian of the Genome: An Alternative RAG/Transib Co-Evolution Hypothesis for the Origin of V(D)J Recombination - Yakovenko, Iryna; Agronin, Jacob; Smith, L. Courtney; Oren, Matan (Frontiers in Immunology, 2021)
The appearance of adaptive immunity in jawed vertebrates is termed the immunological ‘Big Bang’ because of the short evolutionary time over which it developed. Underlying it is the recombination activating gene (RAG)-based V(D)J recombination system, which initiates the sequence diversification of the immunoglobulins and lymphocyte antigen receptors. It was convincingly argued that the RAG1 and RAG2 genes originated from a single transposon. The current dogma postulates that the V(D)J recombination system was established by the split of a primordial vertebrate immune receptor gene into V and J segments by a RAG1/2 transposon, in parallel with the domestication of the same transposable element in a separate genomic locus as the RAG recombinase. Here, based on a new interpretation of previously published data, we propose an alternative evolutionary hypothesis suggesting that two different elements, a RAG1/2 transposase and a Transib transposon invader with RSS-like terminal inverted repeats, co-evolved to work together, resulting in a functional recombination process. This hypothesis offers an alternative understanding of the acquisition of recombinase function by RAGs and the origin of the V(D)J system.